2014
DOI: 10.1007/s11356-014-2729-7
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and photocatalytic decomposition of roxarsone by TiO2 and its mechanism

Abstract: Roxarsone (3-nitro-4-hydroxyphenylarsonic acid) has been widely used as organic arsenic additive in animal industry. In this study, the adsorption of roxarsone on TiO₂ under dark conditions, the photocatalytic decomposition of roxarsone under UV/TiO₂, and the possible photocatalytic pathway were investigated. At the initial concentration of 5-35 mg/L, the adsorption of roxarsone fitted well with the pseudo-second-order kinetics. The isotherms analysis showed that the Langmuir model was better than the Freundli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Transformation of organoarsenicals in advanced oxidation processes (AOPs) has been studied for the UV-H 2 O 2 system (Czaplicka et al, 2014;Zhu et al, 2014) and UV-TiO 2 photodegradation (Zheng et al, 2010(Zheng et al, , 2013Lu et al, 2014). In general, oxidation of organoarsenicals in these systems stems from reaction with hydroxyl radicals.…”
Section: Treatment Options For Organoarsenical-laden Wastementioning
confidence: 99%
“…Transformation of organoarsenicals in advanced oxidation processes (AOPs) has been studied for the UV-H 2 O 2 system (Czaplicka et al, 2014;Zhu et al, 2014) and UV-TiO 2 photodegradation (Zheng et al, 2010(Zheng et al, , 2013Lu et al, 2014). In general, oxidation of organoarsenicals in these systems stems from reaction with hydroxyl radicals.…”
Section: Treatment Options For Organoarsenical-laden Wastementioning
confidence: 99%
“…Its adsorption mechanisms involve surface complex, electrostatic interactions and so on [12][13][14]. Although organoarsenic adsorption with natural particles is not realized its structural transformation, the abiotic processing is regarded as a prerequisite for organoarsenic decomposition [15,16]. For example, Cheng et al investigated p-ASA transformations on birnessite (δ-MnO 2 ), and found that p-ASA was efficiently degraded via the formation of p-ASA radicals through single-electron transfer to δ-MnO 2 and subsequent cleavage of the C-As bond [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in a study in China that the content of arsenic in the pig manure and chicken litter were 89.3 and 21.6 mg/kg, respectively [5]. Organic arsenic compounds are transformed into inorganic arsenic compounds through both biotic and abiotic pathways [2,6,7]. Under anaerobic conditions, organic arsenic compounds were slowly degraded into inorganic arsenic compounds, including arsenite (As(III)) and arsenate (As(V)), and As(III) was the main species [2,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%